PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HIGHER ORDER THINKING SKILLS (HOTS) PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V SD IT UNGGULAN MAWADDAH MAKASSAR - Ria Adriana Amir; Hardianto Rahman; Hardiyanti Hatibu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low Higher Order Thinking Skills (HOTS) of students. Therefore, an innovative learning model is needed to improve students' HOTS, one of which is the Problem Based Learning (PBL) model that emphasizes contextual problem-solving activities. This study aimed to: (1) determine the implementation of the Problem Based Learning (PBL) model in developing the Higher Order Thinking Skills (HOTS) of fifth-grade students at SD IT Unggulan Mawaddah Makassar; (2) determine students' HOTS before and after the implementation of the PBL model; and (3) examine the effect of the PBL model on students' HOTS. This research employed a Pre-Experimental Design using the One Group Pretest-Posttest Design. The population consisted of all fifth-grade students of SD IT Unggulan Mawaddah Makassar. The sampling technique used was saturated sampling, involving 20 students as research participants. The research instruments were observation sheets and tests. Data obtained from the pretest, treatment, and posttest were analyzed using descriptive and inferential statistics with Statistical Package for Social Sciences (SPSS) version 25. The results showed that students' HOTS increased from the pretest category of sufficient to the posttest category of good. Thus, it can be concluded that the implementation of the Problem Based Learning (PBL) model had a positive and significant effect on improving the Higher Order Thinking Skills (HOTS) of fifth-grade students at SD IT Unggulan Mawaddah Makassar.